2013
DOI: 10.1016/j.hrtlng.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias in patients with acute coronary syndrome in the first 24 hours of hospitalization

Abstract: Objectives In patients with acute coronary syndrome (ACS), we sought to: 1) describe arrhythmias during hospitalization, 2) explore the association between arrhythmias and patient outcomes, and 3) explore predictors of the occurrence of arrhythmias. Methods In a prospective sub-study of the IMMEDIATE AIM study, we analyzed electrocardiographic (ECG) data from 278 patients with ACS. On emergency department admission, a Holter recorder was attached for continuous 12-lead ECG monitoring. Results Approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
0
21
2
Order By: Relevance
“…130 Nonetheless, because ventricular arrhythmias are known to occur Patients with Class I indications for arrhythmia monitoring who need to be transported off the unit should have continuous electrocardiographic monitoring via a portable monitor-defibrillator/pacemaker with a healthcare provider skilled in use of the equipment and in electrocardiographic interpretation.…”
Section: Early Phase Of Acs (<24 Hours)mentioning
confidence: 99%
See 1 more Smart Citation
“…130 Nonetheless, because ventricular arrhythmias are known to occur Patients with Class I indications for arrhythmia monitoring who need to be transported off the unit should have continuous electrocardiographic monitoring via a portable monitor-defibrillator/pacemaker with a healthcare provider skilled in use of the equipment and in electrocardiographic interpretation.…”
Section: Early Phase Of Acs (<24 Hours)mentioning
confidence: 99%
“…Despite the recommendation of the ACC/ AHA guidelines for revascularization in these patients, nearly 20% of patients with non-STsegment elevation ACS and either 3vessel disease or left main disease identified with coronary angiography during hospital ization, who are known to benefit from revasculariza tion, were managed medically. 161 During the first 24 hours of admission for patients with ACS, of whom 73% did not undergo PCI, Winkler et al 130 found that potentially lifethreatening arrhythmias occurred rare ly: <1% developed asystole, TdP, or VF, and only 1% had sustained VT. In this sample, 8.63% were diag nosed with STEMI, 26.62% with NSTEMI, and 64.75% with unstable angina.…”
Section: After MI Without Reperfusion or Revascularizationmentioning
confidence: 99%
“…Recently, Winkler and colleagues 8 studied 278 patients diagnosed with ACS to determine the potential benefits of ST-segment monitoring in the ED; they found the incidence of ventricular arrhythmias (premature ventricular contractions, nonsustained ventricular tachycardia, and malignant arrhythmias) over the first 24 hours of hospitalization to be lower than studies conducted before the reperfusion era in the late 1980s.…”
Section: Arrhythmia Monitoring In the Emergency Departmentmentioning
confidence: 99%
“…22 Higher rates of asystole or EMD have been reported in STEMI. 23 Rates of complete heart block have been previously reported as high as 2% to 5%, 1317 and this is in part due to inclusion of STEMI patients.…”
Section: Discussionmentioning
confidence: 91%